Line-Field Confocal Optical Coherence Tomography of Plaque Psoriasis Under IL-17 Inhibitor Therapy: Artificial Intelligence-Supported Analysis - Wirsching, Hanna B.; Mayer, Oliver J.; Schlingmann, Sophia; Thamm, Janis R.; Schiele, Stefan; Rubeck, Anna; Heinz, Wera; Welzel, Julia; Schuh, Sandra (Applied sciences, 2025)
To date, therapeutic responses in plaque psoriasis are evaluated with clinical scores. No objective examination has been established. A recently developed non-invasive imaging tool, line-field confocal optical coherence tomography (LC-OCT), enables the in vivo live imaging of skin changes in psoriasis under therapy. The aim of this study was to measure therapeutic response clinically and with LC-OCT, comparing the subjectively scored epidermal changes with an AI-supported analysis. This prospective, observational study included 12 patients with psoriasis starting a systemic treatment with IL-17 inhibitors (secukinumab, ixekizumab, and bimekizumab). LC-OCT and clinical assessment with a local psoriasis and severity index of the study plaque and a control area were performed before the initiation of therapy as well as after 4 and 12 weeks of treatment. A manual and AI-supported measurement of the thickness of epidermis, stratum corneum, and undulation of the dermo-epidermal junction was carried out. Acanthosis and hyperkeratosis showed a significant reduction under treatment. AI-supported calculations were compared to subjective measurements showing good reliability with high correlation. AI-supported analysis of vascular changes may serve as a prognostic and therapeutic response marker in the future.